Optimization of Perturb and Observe Algorithm Efficiency in MPPT PV Array System Using Boost Converter: A Simulink-Based Investigation - Abdillah Aziz Muntashir; Prasetyani, Lin; Surawan Setiyadi; M. Irkam Baihaqi (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2025)
The increasing demand for renewable energy requires efficient power conversion and control strategies to maximize the utilization of photovoltaic (PV) systems. Among various approaches, Maximum Power Point Tracking (MPPT) is critical in ensuring optimal energy extraction under varying irradiance and load conditions. This study focuses on optimizing the efficiency of the Perturb and Observe (P&O) algorithm implemented in a PV array system with a DC–DC boost converter. A comprehensive Simulink-based investigation is conducted to analyze the algorithm’s performance in terms of tracking speed, stability, and steady-state oscillation. The results demonstrate that the optimized P&O method significantly improves the dynamic response of the boost converter while maintaining high tracking accuracy under irradiance fluctuations and load variations. Furthermore, this work is presented as a preliminary study prior to the integration of MPPT control with a PLC-based monitoring system, providing a reliable foundation for real-time industrial applications. The findings contribute to the enhancement of PV system efficiency and offer valuable insights for future implementation in smart energy management platforms.